2021
DOI: 10.1083/jcb.202103154
|View full text |Cite
|
Sign up to set email alerts
|

A cryo-ET survey of microtubules and intracellular compartments in mammalian axons

Abstract: The neuronal axon is packed with cytoskeletal filaments, membranes, and organelles, many of which move between the cell body and axon tip. Here, we used cryo-electron tomography to survey the internal components of mammalian sensory axons. We determined the polarity of the axonal microtubules (MTs) by combining subtomogram classification and visual inspection, finding MT plus and minus ends are structurally similar. Subtomogram averaging of globular densities in the MT lumen suggests they have a defined struct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 199 publications
(285 reference statements)
10
60
0
Order By: Relevance
“…This is in agreement with previous studies showing that microtubules have the same polarity in axons and mixed polarity in dendrites, which serves to separate axonal and dendritic cargo trafficking, as kinesins move towards the plus end dyneins towards the minus end ( van Beuningen and Hoogenraad, 2016 ). While this was confirmed in axons of cultured mouse neurons, it was reported that 32% of axons in Drosophila primary culture contained microtubules of mixed polarity ( Foster et al, 2022 ). Furthermore, whereas virtually all microtubules were formed of 13 protofilaments in mouse neurons, about half of the microtubules in Drosophila consisted of 12 protofilaments and the other half of 13 protofilaments.…”
Section: Cell-ubiquitous Components Visualized In Neuronsmentioning
confidence: 82%
See 4 more Smart Citations
“…This is in agreement with previous studies showing that microtubules have the same polarity in axons and mixed polarity in dendrites, which serves to separate axonal and dendritic cargo trafficking, as kinesins move towards the plus end dyneins towards the minus end ( van Beuningen and Hoogenraad, 2016 ). While this was confirmed in axons of cultured mouse neurons, it was reported that 32% of axons in Drosophila primary culture contained microtubules of mixed polarity ( Foster et al, 2022 ). Furthermore, whereas virtually all microtubules were formed of 13 protofilaments in mouse neurons, about half of the microtubules in Drosophila consisted of 12 protofilaments and the other half of 13 protofilaments.…”
Section: Cell-ubiquitous Components Visualized In Neuronsmentioning
confidence: 82%
“…Such a level of detail had never been visualized in plastic-embedded samples. Recently, loosely packed cytoskeletal arrays were revealed in mammalian dorsal root ganglion axons, containing intermediate filaments, microtubules, actin, and an unknown type of thin filaments, which the authors hypothesized were made by spectrins ( Foster et al, 2022 ).…”
Section: Cell-ubiquitous Components Visualized In Neuronsmentioning
confidence: 99%
See 3 more Smart Citations